THE INFLUENCE OF INTERNAL AND EXTERNAL FACTORS ON BANK LENDING - Muhammad Akbar (Indonesian Journal of Multidisciplinary Science, 2023)
The purpose of this study was to analyze the influence of internal and external factors on bank lending. Internal factors in this study are CAR, DPK, LDR, and NPL. Meanwhile, the external factors used are GDP and JIBOR. The sample used is PT. Bank Rakyat Indonesia. The data used in this study was obtained from the quarterly financial statements of bank BRI in the 2017-2021 period and analyzed using the least square method. This study found that the DPK and LDR variables partially had a positive and significant effect on lending, the CAR, NPL, and JIBOR variables did not have a significant effect on lending, and the GDP variables had a negative effect on lending. In contrast, simultaneously the CAR, DPK, LDR, NPL, GDP, and JIBOR variables significantly affected the distribution of PT Bank Rakyat Indonesia.